Introducing the Pseudepigrapha of Second Temple Judaism : message, context, and significance - Gurtner, Daniel M. (Grand Rapids Baker Academic, 2020)
"Introduces students to the pseudepigraphal writings of Second Temple Judaism that are most important for understanding first-century developments"--
Includes bibliographical references (pages 384-417) and index.
Keywords: Apocryphal books (Old Testament) -- Criticism, interpretation, etc